Roman Gems in the National Soares dos Reis Museum in Oporto - Graça Cravinho (Studies in Ancient Art and Civilization, 2018)
The 34 intaglios and cameos discussed in this paper are part of a collection of 136 gems (both Roman and Modern) we studied in 2002, with permission of the former Museum director, Mónica Baldaque, and the curator Fátima Macedo. Some of those gems are set in rings (no. 10 – Roman iron ring; no. 22 – medieval gold ring; no. 31 – modern gold ring; also 3 ceramic cameos depicting the Portuguese Queen Maria I – modern silver rings: inv. nos 74 CMP; 75 CMP and 174 MNSR) and 2 others in snuff boxes (1 ivory cameo and 1 Wedgwood cameo – inv. nos 37 MNSR and 31 MNSR, respectively). Besides them, the museum also holds a collection of 800 plaster seals. Among the types of these Roman gems, some deserve special attention: Marsyas (no. 6) – the only gem in the Portuguese Gem Corpus bearing this theme, as well as those of Athena Promachos (no. 7), Isis-Selene bust (no. 9), Socrates (no. 11), Diogenes (no. 14), eagle fighting a serpent (no. 17), shrimp and murex (no. 19), mouse (23) and confronted doves (no. 25). This last one, with its associated inscription, perhaps symbolizes the union of a couple by the bonds of matrimony. However, how did the scarab bearing a Centaur (no. 28) reach Portugal?